Divalent Titanium via Reductive N−C Coupling of a TiIV Nitrido with π-Acids - Bhunia, Mrinal; Sandoval-Pauker, Christian; Fehn, Dominik; Grant, Lauren N.; Senthil, Shuruthi; Gau, Michael R.; Ozarowski, Andrew; Krzystek, J.; Telser, Joshua; Pinter, Balazs; Meyer, Karsten; Mindiola, Daniel J. (Angewandte Chemie International Edition, 2024)
The nitrido-ate complex [(PN)2Ti(N)μ2-K(OEt2)]2 (1) (PN−=(N-(2-PiPr2-4-methylphenyl)-2,4,6-Me3C6H2) reductively couples CO and isocyanides in the presence of DME or cryptand (Kryptofix222), to form rare, five-coordinate TiII complexes having a linear cumulene motif, [K(L)][(PN)2Ti(NCE)] (E=O, L=Kryptofix222, (2); E=NAd, L=3 DME, (3); E=NtBu, L=3 DME, (4); E=NAd, L=Kryptofix222, (5)). Oxidation of 2–5 with [Fc][OTf] afforded an isostructural TiIII center containing a neutral cumulene, [(PN)2Ti(NCE)] (E=O, (6); E=NAd (7), NtBu (8)) and characterization by CW X-band EPR spectroscopy, revealed unpaired electron to be metal centric. Moreover, 1e− reduction of 6 and 7 in the presence of Kryptofix222cleanly reformed corresponding discrete TiII complexes 2 and 5, which were further characterized by solution magnetization measurements and high-frequency and -field EPR (HFEPR) spectroscopy. Furthermore, oxidation of 7 with [Fc*][B(C6F5)4] resulted in a ligand disproportionated TiIV complex having transoid carbodiimides, [(PN)2Ti(NCNAd)2] (9). Comparison of spectroscopic, structural, and computational data for the divalent, trivalent, and tetravalent systems, including their 15N enriched isotopomers demonstrate these cumulenes to decrease in order of backbonding as TiII→TiIII→TiIV and increasing order of π-donation as TiII→TiIII→TiIV, thus displaying more covalency in TiIII species. Lastly, we show a synthetic cycle whereby complex 1 can deliver an N-atom to CO and CNAd.
CRIS-Team Scopus Importer:2024-07-12
Keywords: atom transfer; nitride; reactivity; reductive coupling; structural interpretation; titanium